Foreword - Epure, Manuela (Journal of Economic Development, Environment and People, 2019)
Globalization shapes our lives in a great extent: we work from 9 to 5, having our co-workers located in different countries, we eat food coming from various location all over the world, we use communication devices made in some Asian countries, and we share happy or sad moments with “friends” that we have never seen before. Internet connectivity becomes more and more an indispensable Is this about global citizenship, the sense of belonging to the global community is more powerful than citizenship itself. Recently, the DHL Global Connectedness Index [1] reveals that the world ended 2017 more globalized than ever, despite the predictions and the Brexit and Trump shock waves. The year 2018 brought new obstacles, such as tariff tiffs, the global business competition is still on track. The executives must think to build their business in new coordinates that might overcome today’s turbulences. More than ever, successful business decisions should rely on accurate perceptions of the environment, and a clear-eyed view of how globalization measures are trending. The Netherlands is the world’s most globally connected country. Singapore leads on the size of its international flows relative to domestic activity, while the United Kingdom has the most global distribution of flows around the world. Countries that integrate more deeply into international flows tend to enjoy faster economic growth and even the top-ranked countries have untapped opportunities to strengthen their global connectedness..... [1] Altman, S., Ghemawat, P. Bastian Ph. – DHL Global Connectedness Index 2018: The State of Globalization in a Fragile World